Indonesian molasses export supply in world trade - Muhammad Teguh Iman Aris Bandriyo; Yusman Saukat; Amzul Rifin (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study examines the factors affecting Indonesian molasses exports in international trade using time series data from 2003 to 2019. The analysis tool used is the Error Correction Model (ECM). The analysis results show that in the long run, the variables of molasses production, exchange rates, and inflation have a significant effect on Indonesia's molasses export supply. In contrast, Indonesia's GDP, molasses export prices, and world CPO prices have no significant effect. In the short run, the variables of molasses production, world molasses prices, exchange rates, and inflation have a significant effect. The variables of Indonesia's GDP, molasses export prices, and world CPO prices have no significant effect on Indonesia's molasses export supply in world trade.